Antibiotic Resistances and Drug Delivery System Used To Combat Antibiotic Resistance - Sharma, Shrestha; Kumar, Vinod; Khan, Naved (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this review is to explore and discuss the situational analysis of antibiotic resistance along with the various challenges and different strategies required to reduce this burden in developing countries. Researchers found that this is an alarming condition because diseases caused by bacteria/microbes become harder to treat. However, the main reasons for resistance are non-judicial use of antibiotics, withdrawal therapy, imbalance of antibiotic consumption, etc. Literature searched from various search engines like Google search, Medline, and other authenticated sources was reviewed and analysed and suggested that we need to educate the patients and public regarding the antibiotic resistance.